A Novel and Expedient Approach to New Thiazoles, Thiazolo[3,2-a]pyridines, Dihydrothiophenes, and Hydrazones Incorporating Thieno[2,3-b]thiophene Moiety - Mabkhot, Yahia Nasser (Molecular Diversity Preservation International (MDPI), 2012)
This paper reports details about the synthesis of a series of novel functionalized symmetrical bis-heterocyclic compounds containing a thieno[2,3-b]thiophene motif. Bis-thiazole derivatives 2, 3a-c and thiazolo[3,2-a]pyridine derivatives 4a-c are achieved. The hitherto unknown dihydrothiophene derivatives 6a-d via bis-pyridimium salt 5 are obtained. Additionally, the novel hydrazonothieno[2,3-b]thiophene derivatives 10a-c are obtained via bis-tosylacetylthieno[2,3-b]thiophene derivative 9. All compounds are characterized by (1)H-, (13)C-NMR, GCMS, IR, and UV-vis spectrometry. These compounds represent a new class of sulfur and nitrogen containing heterocycles that should also be of interest as new materials.